DUKUNGAN KELUARGA PADA KEKAMBUHAN PENYALAHGUNA NARKOTIKA - Filia Linda Hapsari; Induniasih (MEDIA ILMU KESEHATAN, 2012)
Background : Drug abuse is one of the cause death, there is 15.000 every year.Report of BNK Yogyakarta the case of drug abuse are 12.848 students of elementary school; 110.870 of junior high school and senior high school students. Relapse is one of the effect drug of abuse that cause addiction for both acute/ cronic disease. The factor that influence of relapse is family support. Family support can make relap sedecreasing. Objective: This study aimed to determine the relationship between family support and relapse of drug abuser in the Social Institution Pamardi Putra Purwomartani Kalasan Sleman Yogyakarta. Method: The study was kuatitative non eksperimental with observasional cross sectional design. Population of drug abuse that lead rehabitation in Social Institution Pamardi Putra Purwomartani were 24 people. The analysis technique used Spearman Rank to see the variables relation and correlation coefficient test would use to find out the strenght of relation. The research was conducted in Social Institution Pamardi Putra Purwomartani on July 18 th, 2011. Result: on this study, there were 24 respondents.The respondent who had moderate family support was 50% with high relapsing 54,2%. There was any relation between family suport and relapse of drug abuser, with significant value 0,802. That indicate strenght relation. Conclusion: There is any relation between family support and relapse of drug abuser in Social Institution Pamardi Putra Purwomartani Kalasan Sleman Yogyakarta. Keyword: Familysupport, relapse,drugabuser